A dança como conteúdo da educação física escolar: uma análise a partir da perspectiva de professores do Ensino Fundamental do município de Castanhal-PA - LOBATO, Alaila Rodrigues (2019)
The present study has as general objective, to analyze how Physical Education teachers of elementary education in the municipality of Castanhal - Pa are exploring the dance content in Physical Education classes. To this end, the research is classified in qualitative and is characterized as a field research. The sample of the present study was composed of 12 Physical Education teachers, of whom 06 were female and 06 were male. Teachers had the age group of 25 to 42, in which 07 worked in private schools and 05 in public schools of the Municipality of Castanhal-PA. As an instrument of data collection, a questionnaire was used with eight questions (open and closed) in which we sought to identify the relationship between teachers and dance. The results of the research led us to understand that, although dance as content is being worked on, it is remarkable the need to continue advancing, because, the dance in the classes of Physical Education is the subject that has always innovated the practice of this discipline.